Strategi Pengembangan Objek Wisata Bukit Matang Kaladan Desa Tiwingan Lama Kab. Banjar Provinsi Kalimantan Selatan di Era New Normal - Alfiyanor, Alfiyanor; Rahmini, Noor (PPJP Universitas Lambung Mangkurat, 2023)
This study aims :(1) to determine the potential advantages of the hill Matangkaladan tourist attraction in the new average era. (2) To analyze the strategies that must be carried out to increase the number of tourist visits to the hill Matang Kaladan tourist attraction in the new average era. In this study, six respondents were considered to have an influence and role in developing the Matangkaladan Hill tourist attraction. The results of this study indicate that the potential advantages of the tourist attraction of Matang Kaladan are its beautiful natural scenery and complete facilities. The strategy that was produced in this study was the S-O. (1) strategy continues to maintain the unique and attractive natural beauty and hold attractions to increase tourist visits with easy-to-reach locations of the CHSE program to improve the safety and comfort of visitors during the COVID-19 period 19. (2) Increasing the achievement of leading tourism is capital to compete with other leading tourism throughout Indonesia through extensive social media and implementing the CHSE program to ebecome a leading tourist in the Covid-19 period.